Characterization of guinea pig T cell responses elicited after EP-assisted delivery of DNA vaccines to the skin. Issue 1 (3rd January 2017) - Schultheis, Katherine; Schaefer, Hubert; Yung, Bryan S.; Oh, Janet; Muthumani, Karuppiah; Humeau, Laurent; Broderick, Kate E.; Smith, Trevor R.F.
Highlights: Development of an IFN-γ ELISpot to detect peripheral T cell responses in guinea pigs. Delineation of T cell responses in guinea pigs after vaccine delivery to the skin. Identification of conserved T cell epitopes across an outbred guinea pig population. Abstract: The skin is an ideal target tissue for vaccine delivery for a number of reasons. It is highly accessible, and most importantly, enriched in professional antigen presenting cells. Possessing strong similarities to human skin physiology and displaying a defined epidermis, the guinea pig is an appropriate model to study epidermal delivery of vaccine. However, whilst we have characterized the humoral responses in the guinea pig associated with skin vaccine protocols we have yet to investigate the T cell responses. In response to this inadequacy, we developed an IFN-γ ELISpot assay to characterize the cellular immune response in the peripheral blood of guinea pigs. Using a nucleoprotein (NP) influenza pDNA vaccination regimen, we characterized host T cell responses. After delivery of the DNA vaccine to the guinea pig epidermis we detected robust and rapid T cell responses. The levels of IFN-γ spot-forming units averaged approximately 5000 per million cells after two immunizations. These responses were broad in that multiple regions across the NP antigen elicited a T cell response. Interestingly, we identified a number of NP immunodominant T cell epitopes to be conserved across an outbred guinea pig population, a phenomenon which was also observed after immunization with a RSV DNA vaccine. We believe this data enhances our understanding of the cellular immune response elicited to a vaccine in guinea pigs, and globally, will advance the use of this model for vaccine development, especially those targeting skin as a delivery site.